2022
DOI: 10.3389/fimmu.2022.940645
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell RNA sequencing reveals distinct immunology profiles in human keloid

Abstract: Keloids, characterized by skin fibrosis and excessive accumulation of extracellular matrix, remain a therapeutic challenge. In this study, we systematically capture the cellular composition of keloids by the single-cell RNA sequencing technique. Our results indicated that there are significant differences in most cell types present between 12 pairs of keloid and adjacent normal tissue. We found that fibroblasts, endothelial cells, mast cells, mural cells, and Schwann cells increased significantly in keloid. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
35
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 61 publications
3
35
0
Order By: Relevance
“…Single-cell sequencing findings have confirmed that MS4A7 is highly expressed in some macrophages (24), and can be used as an immune signature to predict ovarian cancer prognoses (25).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Single-cell sequencing findings have confirmed that MS4A7 is highly expressed in some macrophages (24), and can be used as an immune signature to predict ovarian cancer prognoses (25).…”
Section: Discussionmentioning
confidence: 84%
“…Single-cell sequencing findings have confirmed that MS4A7 is highly expressed in some macrophages ( 24 ), and can be used as an immune signature to predict ovarian cancer prognoses ( 25 ). SPARC, a CR-mimetic adipokine, induces inflammatory interferon response in macrophages during aging ( 26 ).…”
Section: Discussionmentioning
confidence: 91%
“…Dysregulation of this process leads to either prolonged inflammation with delayed wound closure or increased scarring. M2 macrophages are disproportionally elevated in keloid lesions ( 69 – 72 , 74 ), in part due to local enrichment of Th2 cytokines. Although not yet verified, M2 dominance has also been linked to macrophage sensitivity to mechanical signals, including skin tension and stiffness ( 42 ).…”
Section: The Roles Of Immune Cells In Keloid Formationmentioning
confidence: 99%
“…On the other hand, reduced expression of potential anti-inflammatory mediators, such as IL-34 and IL-37, has been reported ( 85 , 87 , 95 , 96 ). Single-cell RNA sequencing and spatial transcriptomics ( 72 , 97 99 ), as well as epigenetics ( 34 , 100 ) are emerging fields utilized to reveal potential pathophysiological features of keloids. One single-cell RNA sequencing study identified a distinct macrophage-centered communication regulatory network that may favor transition and proliferation of M2 macrophages ( 72 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation